UMAR’S ASSURANCE OF AMAN TO THE PEOPLE OF AELIA (BAYT AL-MAQDIS - ISLAMICJERUSALEM): A CRITICAL ANALYTICAL STUDY OF AL-TABARI’S VERSION - El-Awaisi, Abd al-Fattah (Journal of Al-Tamaddun, 2018)
The first Muslim Fatih of Bayt al-Maqdis (Islamicjerusalem) was an event both remarkable and long-lasting in its effects. It is viewed as a fundamental landmark event which reshaped the relationships between the people of diverse faiths who inhabited the region. In the few academic studies on this first Muslim Fatih, AI-Uhda al-Umariyya or Umar’s Assurance of Aman to the people of Aelia (Bayt al-Maqdis - Islamicjerusalem) is regarded as being a major turning point in both historic, juristic and international relations terms. Far from being a study of this first Muslim Fatih, the objective of this article is namely to critically examine the authenticity of Umar’s Assurance and compare most of the available early versions of Umar’s Assurance, hoping to identify the early version which could be argued to be the most authentic as Umar’s original text. It focuses mainly on one of its longest and most famous versions, namely the text given by al-Tabari. It concludes that al-Tabari version of the Assurance, but without an added restrictive sentence, is Umar’s original text that he wrote and witnessed for the people of Bayt al-Maqdis (Islamicjerusalem). As this research focused mainly on al-Tabari’s version, it is hoped that this article will encourage scholars to examine the other versions of the Assurance and develop further the reasons behind the appearance of various versions of Umar’s Assurance.